Solving for project risk management : understanding the critical role of uncertainty in project management - Smart, Christian (McGraw Hill, 2021)
"From a top risk analyst on major NASA and DoD projects-the concepts, information, and approaches you need to dramatically reduce financial risk on any project, in any industry Even when a quantitative approach to risk management is taken, the process is fraught with obstacles, including a lack of understanding of uncertainty and ignorance of actual risk levels, peoples' inherent biases that cause them to underestimate risk, and disconnection of staff and teams involved in the process. Ideal for project managers, business analysts, and senior decision makers in both the public and private sectors, Solving for Project Risk Management explains why standard cost and schedule management practices are sub-par and offers practical guidance on how to fix them. With heavy emphasis on risk management and understanding the role of uncertainty, this comprehensive guide provides everything readers need to ensure project success by conducting risk management the right way. Whatever the size or complexity of a project, the failure to manage it with diligence and know-how can-and often does-lead to devastating consequences for an organization. Chapters include: The Enduring Problem of Cost and Schedule Growth The Quantitative Cost and Schedule Risk Imperative Incorporating Realism in Risk Analysis Considering the Right Tail in Risk Management The Need for Portfolio Management Smart lays out common problems and explains how to solve them for positive outcomes, including how to use uncertainty to make better decisions, and employs narrative and personal experience to illustrate key concepts. Whatever the size or complexity of a project, the failure to manage its inherent risk with diligence and know-how can-and often does-lead to devastating consequences for an organization. Solving for Project Risk Management delivers everything you need to ensure your projects run smoothly and deliver the expected value to your organization"--